2014
DOI: 10.3168/jds.2014-8467
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nitrogen, phosphorus, and potassium mass balances of dairy farms in New York State

Abstract: A whole-farm nutrient mass balance (NMB) is a useful measure of the nutrient status of a dairy farm. Research is needed to define and determine a feasible NMB range for dairy farm systems in New York State (NY). The objectives of this study were to (1) document the distribution of N, P, and K mass balances of 102 NY dairy farms (including 75 small, 15 medium, and 12 large farms); (2) establish initial NMB benchmarks based on what 75% of the farms achieved; (3) determine the maximum animal density that allows a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 37 publications
5
75
1
3
Order By: Relevance
“…Liquid manure from the dairy has been applied to the soil via injection since 1994. Manure was the only fertilizer nutrient source on this farm from 2007 onwards (Ketterings 2014). The farm seeds winter cereals as cover crops annually on as many corn silage acres as possible (weather determined).…”
Section: Study Site and Management Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid manure from the dairy has been applied to the soil via injection since 1994. Manure was the only fertilizer nutrient source on this farm from 2007 onwards (Ketterings 2014). The farm seeds winter cereals as cover crops annually on as many corn silage acres as possible (weather determined).…”
Section: Study Site and Management Practicesmentioning
confidence: 99%
“…In the past 10 years, the proportion of forages as a percent of the total ration dry matter (DM) in Northeast dairy farm rations has increased from less than 50 % of the total DM to 55-70 % forage as a percent of the total ration DM (Chase and Grant 2013). Assessments of 102 NY dairy farms in 2006 showed that nearly all the forages fed were produced on the farm (homegrown forages) reducing the farm's cost of production and environmental footprint and increasing its whole-farm nutrient use efficiency (Cela et al 2014). The predominant forages grown for dairy cow rations in NY are corn (Zea mays L.) silage and alfalfa (Medicago sativa L.) and grass hay mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…The K concentrations showed the greatest variability (1.03 to 3.35% of DM) and included 4 observations (2.0% of the data), which were greater than 3.0% of DM. Considering macrominerals are generally overfed (Castillo et al, 2013) and dietary K can increase up to 3.0% of DM in some US commercial dairy operations (Cela et al, 2014), those observations of high macromineral contents were included in the data set. The dietary Na concentrations were in line with the ranges of commercial farms (e.g., 0.25 and 0.58% of DM at the 10th and 90th percentiles; Castillo et al, 2013).…”
Section: Models With Mineral Andmentioning
confidence: 99%
“…Typical forage rotations on dairy farms in the state include 3 to 4 yr of corn followed by 3 to 4 yr of mixed alfalfa (Medicago sativa L.)/grass hay. Although corn silage yields have slowly increased over the past 50 yr (National Agricultural Statistics Service, 2016), recent work has shown that double cropping of corn silage with winter cereals such as cereal rye and triticale has the potential to increase overall yield beyond what could be obtained with corn silage only (Ketterings et al, 2015a(Ketterings et al, , 2015b, reducing the need for feed purchases and improving whole farm mass nutrient balances (Cela et al, 2014;Soberon et al, 2015).…”
mentioning
confidence: 99%